Revisiting the Role of Post-Materialist Values on Environmental Concern: An Analysis of Turkish Public Perception Over Climate Change Between the Years 2018-2020 - Yıldız, Tuğçe (Journal of Applied And Theoretical Social Sciences, 2022)
Previous studies on public environmental concerns indicate that economic factors have an impact on individuals’ environmental concerns and attitudes toward environmental problems. Yet, few studies have examined the possible impact of changing economic conditions due to economic and/or financial crises on public environmental concern and especially concern towards climate change. The economic crisis starting in late 2018 in Turkey provides an interesting case to understand the impact of economic factors on environmental concerns and especially attitudes towards climate change. The study asks how changing economic conditions due to the economic crisis of 2018 affected Turkish individuals’ concerns about the climate change problem. Multilevel analysis was applied to data collected from special Eurobarometer surveys between the years 2018 and 2020. The main finding in this study is that changes in the economic situation across Turkey during the crisis period do have an impact in decreasing public concern towards climate change in Turkey overall. In 2020 when the negative effects of economic recession were felt strongly, the results indicate that environmental concern is negatively correlated with the public perceptions of the national economy, household financial situation, and life satisfaction. In other words, while the prioritization of economic factors by most of the society in the period when the economic crisis was most felt, confirms the post-materialist thesis; on the other hand, the increasing awareness of the climate change crisis has started to bring the idea that the exit plans from the economic crisis should be more environmentally friendly and more sustainable.